Rate and determinants of cesarean delivery in northwest of iran: descriptive results from public health records - Kheirouri, Sorayya; Alizadeh, Mohammad; Akbari, Zahra; Ghalehghir, Sanaz; Feizian, Masumeh; Shoae, Zahra (Progress in Nutrition, 2020)
Objective: We investigated socio-demographic, antenatal and neonatal nutritional factors that might contribute to the increased risk of cesarean delivery in Iranian women. Methods: This descriptive study was carried out in Tabriz city, Iran, during June to August 2014. The data of 807 urban mothers delivering a singleton live infant and their offspring were collected from databases of eight primary health care centers and analyzed using spearman’s rank test, univariable and multivariable logistic regression. Results: Cesarean section rate was 55.9%. Higher rates of cesarean section was observed among mothers aged ≥ 35 years (63.2%), with pre-pregnancy weight ≥ 65 kg (62.3%), higher educated (75.0%), high economic status (68.8%), with LBW infants (75.7%), early term delivery (74.9%), and mothers with newborns head circumference (HC) ≥ 34 cm (58.9%). According to multivariate analysis, maternal advanced age (OR= 1.59; 95 % CI 0.99, 2.57; p= 0.05), maternal pre-pregnancy weight ≥ 65 kg (OR= 1.47; 95 % CI 1.08, 1.99; p= 0.01), maternal higher education (OR= 3.49; 95 % CI 1.80, 6.75; p= 0.0001), middle economic status (OR= 1.66; 95 % CI 1.13, 2.43; p= 0.009), early term delivery (OR= 7.11; 95 % CI 5.00, 10.10; p= 0.0001) and newborns HC ≥ 34 cm (OR= 2.08; 95 % CI 1.38, 3.14; p= 0.001) were independently associated with increased odds of cesarean section. Conclusion: The high cesarean rate in Iran must be paid substantial attention. Considering the contributing factors in the incidence of cesarean section, appropriate policies must be adopted to improve quality of maternal care services and to implicate community based health education interventions.